Common misconceptions in mathematics : strategies to correct them - Ojose, Bobby (b)
This handy tool for teachers of mathematics confronts the problem of misconceptions that are common with students that often have their own notion of certain mathematical concepts, right or not. The book is meant for teachers helping students engage in mathematics that emphasizes conceptual understanding.
Includes bibliographical references (pages 126-133).
Keywords: Mathematics; Mathematics -- Study and teaching; Mathematics; Mathematics -- Study and teaching